2002
DOI: 10.1164/rccm.2112077
|View full text |Cite
|
Sign up to set email alerts
|

A Reiterative Method for Calculating the Early Bactericidal Activity of Antituberculosis Drugs

Abstract: Studies of early bactericidal activity (EBA) are important in the rapid evaluation of new antituberculosis drugs. Historically, these have concentrated on the log fall in the viable count in sputum during the first 48 hours of therapy. In this paper, we provide a mathematical model that suggests that the viable count in sputum follows an exponential decay curve with the equation V = S + Me(-kt) (where V is the viable count, M the population of bacteria susceptible to the test drug, S the population susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Extended early bactericidal activities (EBAs) from days 3 to 14 were also comparable, with Ϫ0.082 log 10 (Ϫ0.119, Ϫ0.045) and Ϫ0.124 log 10 (Ϫ0.170, Ϫ0.079) for CFU on solid medium and MBL, respectively. These data match other EBA studies measuring treatment response with solid culture (11)(12)(13)(14)(15)(16). The close comparability between MBL and culture contrasts with data for treatment monitoring using the GeneXpert MTB/RIF assay (Xpert; Cepheid, CA, USA).…”
supporting
confidence: 79%
“…Extended early bactericidal activities (EBAs) from days 3 to 14 were also comparable, with Ϫ0.082 log 10 (Ϫ0.119, Ϫ0.045) and Ϫ0.124 log 10 (Ϫ0.170, Ϫ0.079) for CFU on solid medium and MBL, respectively. These data match other EBA studies measuring treatment response with solid culture (11)(12)(13)(14)(15)(16). The close comparability between MBL and culture contrasts with data for treatment monitoring using the GeneXpert MTB/RIF assay (Xpert; Cepheid, CA, USA).…”
supporting
confidence: 79%
“…Monoexponential and biexponential nonlinear models have been proposed to describe the decline in bacterial load over the first 2 months of treatment, with the biexponential model, reflecting two separate phases of decline, having been shown to best fit the data (4,8,25 the decline of the MBL assay-determined bacterial load in this study with the decline of bacterial load reported in other published studies, we used the same methods described in references 4 and 25 to fit and compare different nonlinear models. Nonlinear mixed-effects models were therefore used to analyze the decline in counts in the 111 patients.…”
Section: Methodsmentioning
confidence: 98%
“…At present, the only widely accepted biomarker of treatment response is culture negativity 56 days after the commencement of therapy (18). Some authors have suggested that measuring the decline in the bacterial load may permit the outcome of treatment to be predicted more accurately (4,8).…”
mentioning
confidence: 99%
“…The EBA was calculated for each patient by the formula (log CFU/ml day0 Ϫ log CFU/ml day5 )/5 and is given as the mean Ϯ standard deviation (SD). As recommended by several authors, we defined the EBA as the decrease in log 10 CFU per milliliter of sputum per day during the first 5 days of treatment (3,4).…”
Section: Methodsmentioning
confidence: 99%